Genomic Interrogation of Ancestral Mycobacterium tuberculosis from South India - Narayanan, Sujatha (Infect Genet Evol, 2007)
Mycobacterium tuberculosis is a very important global pathogen. One quarter of the world's TB cases occur in India. The tuberculosis strains isolated from south Indian patients exhibit certain phenotypic characteristics like low virulence in guinea-pigs, resistance to isoniazid, thiophene-2-carboxylic acid hydrazide (TCH) and para-amino salicylic acid (PAS) enhanced susceptibility to H(2)O(2). Besides this, a large percentage of the isolates harbor only a single copy of IS 6110 which makes these strains distinct. Hence we have studied the genotypic characteristics of these strains by using advanced techniques like Deletion Micro array, deletion PCR, allelic discrimination RT-PCR using several lineage specific markers and KatG G13887 (non synonymous) polymorphism along with spoligotyping. The analysis of 1,215 tuberculosis patient isolates from South India revealed that 85.2% belonged to the ancestral lineage of Mycobacterium tuberculosis. Comparative whole-genome hybridization identified six new genomic regions within this lineage that were variably deleted.